Native and modified sago (Metroxylon sagu) starches as an ingredient in the formulation of low glycaemic food product - Zailani, Mohd Alhafiizh; Kamilah, Hanisah; Awang Husaini, Awang Ahmad Sallehin; Awang Seruji, Awang Zulfikar Rizal; Sarbini, Shahrul Razid (Malaysian Society of Applied Biology, 2023)
Native sago starch has a high content of resistant starch (RS) which is associated with low glycaemic and beneficial to individuals with obesity and diabetes. Additionally, the RS is linked to the prebiotic properties exhibited by starch. This study aimed to evaluate the predicted glycaemic index (pGI) and probiotic growth rates of food formulated with native or modified starches in the formulation of a breakfast drink. The sago starch was modified via microwave heat treatment (MHT) with different treatment duration or via pre-treatment followed by MHT. The formulation of food was performed by replacing a portion of wheat starch at percentages of 25, 50, or 75. The pGI was determined by measuring the amount of glucose produced during in vitro digestion. Meanwhile, the probiotic growth rates were conducted by monitoring the optical density of Lactobacillus casei and Bifidobacterium lactis for 24 hr. Comparatively, food formulated with 50 and 75 starch showed lower pGI than other formulations. This was correlated with the increase of RS in food products. Meanwhile, the probiotic growth rates increase for a few of the formulations mostly with a higher pGI or low RS content which is contributed by the accessibility for fermentation to occur. In conclusion, the findings suggest the substitution of 50 wheat flour with native or modified sago starches is sufficient to increase RS content and lower the pGI of formulated food. In the future, investigation of RS components contributing to probiotic growth is needed to enable the exploration of new prebiotics with low glycaemic.